1990
DOI: 10.1016/0950-3528(90)90051-h
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of gut virus infection

Abstract: In summary, the pathogenesis of many gut virus infections remains uncertain. However, human and animal studies indicate that the majority of gut viruses infect villous enterocytes. Viruses appear to have different affinities for enterocytes at different sites on the villus. Infection of enterocytes leads to cell death, extrusion into the lumen, and villous atrophy when the rate of cell production in the crypts cannot keep pace with the rate of enterocyte loss. This results in a reduced surface area as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Rotavirus-induced disease is thought to be caused by a combination of factors (70), including a reduction in epithelial surface area, replacement of mature enterocytes by immature (crypt-like) cells (10,60), an osmotic effect resulting from incomplete absorption of carbohydrates from the intestinal lumen in combination with bacterial fermentation of these nonabsorbed compounds, secretion of intestinal fluid and electrolytes through activation of the enteric nervous system (43), and the secretory effect of NSP4, which is thought to act as a viral enterotoxin (3). During rotavirus infection, there is an enhanced turnover of epithelial cells that is thought to result in the presence of immature cells on the villi (10,60).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus-induced disease is thought to be caused by a combination of factors (70), including a reduction in epithelial surface area, replacement of mature enterocytes by immature (crypt-like) cells (10,60), an osmotic effect resulting from incomplete absorption of carbohydrates from the intestinal lumen in combination with bacterial fermentation of these nonabsorbed compounds, secretion of intestinal fluid and electrolytes through activation of the enteric nervous system (43), and the secretory effect of NSP4, which is thought to act as a viral enterotoxin (3). During rotavirus infection, there is an enhanced turnover of epithelial cells that is thought to result in the presence of immature cells on the villi (10,60).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus-induced diarrhea is thought to be caused by a combination of factors (55), which include a reduction in epithelial surface area, replacement of mature enterocytes by immature (crypt-like) cells (43), an osmotic effect resulting from incomplete absorption of carbohydrates from the intestinal lumen in combination with bacterial fermentation of these nonabsorbed compounds, secretion of intestinal fluid and electrolytes through activation of the enteric nervous system (37), and the effect of the rotavirus nonstructural protein 4 (NSP4), which is thought to act as a viral enterotoxin (1).…”
mentioning
confidence: 99%
“…Rotavirus invades and replicate in the differentiated absorptive columnar cells of the small intestinal epithelium. This results in partial disruption of the intestinal mucosa with loss of microvilli, a decrease in the villus/crypt ratio and an increased intestinal permeability (Salim et al 1990). Several studies have shown that selected probiotics, such as L. rhamnosus GG, L. reuteri, L. casei Shirota and B. lactis Bb12, can shorten the duration of rotavirus diarrhoea by approximately 1 day (Kaila et al 1992;Saavedra et al 1994;Sugita & Togawa 1994;Shomikova et al 1997).…”
Section: Acute Gastro-enteritismentioning
confidence: 94%